Study about Professional Mobility, Satisfaction and Leadership in Academic-scientific Organizations - Miriam Aparicio (Emerging Trends in Disease and Health Research Vol. 8, 2022)
This research work has been done in the field of social and organizational psychology. It is our aim to analyze the factors which influence the levels of satisfaction and achievement reached by those working for scientific organizations and their relationship with professional mobility [1]. Objectifs: i) To observe if there is a significant association between Professional Mobility and General Job Satisfaction, with no distinction between hard and soft sciences (disciplinary fields.); ii) Analyze the relationship between human factors (psychosocial or other existing variables) and professional mobility observed among researchers from different fields (“hard” or “soft” sciences.); iii) The “disciplinary homogenization” (systems of beliefs, expectations and values, which differ according to the field -“hard” or “soft” sciences- associated with socialization and traditions), are linked to a different level of satisfaction according to the different factors psychosocial issues addressed (working atmosphere, perceptions about their jobs, power and influence, research work organization, among others); iv) Know the role of the leader (units’ director or chief) in academic units of research and the management of scientific organizations in relation to the satisfaction of the members of the research group and, also, with professional mobility. Based on a population of teachers from the Cuyo region (N=355 UID - Research & Development Units), a stratified sample was taken from universities and different specialties (5 percent error margin). The research faculty at this time were from the Universidad Nacional de Cuyo in Mendoza, Argentina (N= 53 Research Units), with one chief or director and members. Quantitative methods were employed (two questionnaires). The findings reveal that contentment among researchers varies depending on their professional mobility and disciplinary domains. In terms of leadership and career mobility, researchers, regardless of their disciplinary discipline, express a general sense of pleasure.